2018
DOI: 10.3164/jcbn.17-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic effect of β-caryophyllene in rats fed cholesterol and fat enriched diet

Abstract: Hypercholesterolemia is a major risk factor for cardiovascular diseases. This study investigated the cholesterol-lowering potential of β-caryophyllene in a rat model. Hypercholesterolemia was induced by feeding male Wistar rats a high cholesterol and fat diet for 2 weeks. This was followed by oral administration of β-caryophyllene to hypercholesterolemic rats at 30, 100 and 300 mg/kg b.w. for 4 weeks. A dose of 30 mg/kg of β-caryophyllene significantly lowered serum total cholesterol, low density lipoprotein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 41 publications
1
31
2
Order By: Relevance
“…In contrast to the studies described herein, other investigators have reported hypolipidemic effects of BCP [58][59][60][61]. These observations were detected, in vivo, under both hyperlipidemic and hypercholesterolemic conditions.…”
Section: Resultscontrasting
confidence: 98%
“…In contrast to the studies described herein, other investigators have reported hypolipidemic effects of BCP [58][59][60][61]. These observations were detected, in vivo, under both hyperlipidemic and hypercholesterolemic conditions.…”
Section: Resultscontrasting
confidence: 98%
“…In contrast to the studies described herein, other investigators have reported hypolipidemic effects of BCP (58)(59)(60)(61). These observations were detected, in vivo, under both hyperlipidemic and hypercholesterolemic conditions.…”
Section: Is Cholesterol Content or Redistribution Within The Pm The Kcontrasting
confidence: 99%
“…Moreover, the caffeoylquinic acid had been reported to have antihyperlipidemic mechanism by increasing the expression of PPARalpha and PPARdelta, suppressing adiponectin, and upregulation of LPL and AMPK activities [46][47][48]. Furthermore, it had been reported that beta-caryophyllene, one of the main components in the PIT, could attenuate palmitate-induced lipid accumulation through AMPK signaling and prevent atherosclerosis in hypercholesterolemic rats [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%